Eﬀect of pinching and plant growth regulators on yield and quality of fenugreek (Trigonella foenum-graecum) - Kamlesh Kumar Yadav; DK Rana; TS Bisht; KN Shah; Hemant Kumar Gurjar (Current Horticulture, 2025)
A ﬁeld experiment was conducted to ﬁnd out the eﬀect of pinching and plant growth regulators on yield and quality of fenugreek (Trigonella foenum-graecum L.) cv. Pant Ragini during 2020-21 at Department of Horticulture, H N B Garhwal University, Srinagar (Garhwal), Uttarakhand. Minimum days taken to ﬁrst and 50 % ﬁrst pod formation (89.88 and 93.97 days), signiﬁcantly maximum length of pod (11.23 cm), pod diameter (2.13 mm), pods/plant (51.85), number of seeds/pod (18.92), seed yield/plant (8.02g), seed yield/plot (657.78 g) and seed yield/ha (39.70 q), and quality parameters, viz. TSS (13.08 0Brix) and ascorbic acid (60.73 mg/100g) were recorded with seed soaking of S1 (GA3 50 ppm). Among plant growth regulators, foliar spray of G1 (GA3 50 ppm) twice (30 and 60 DAS) took minimum days to ﬁrst and 50 % ﬁrst pod formation (89.88 and 93.97 days), maximum length of pod (11.23 cm) and pod diameter (2.13 mm), number of pods/plant (51.87), number of seeds/pod (18.85), seed yield/plant (7.86g), seed yield/plot (609.62 g) and seed yield/ha (37.13 q) and quality parameters, viz. TSS (13.75 0Brix) and ascorbic acid (62.29 mg/100g) of diﬀerent pinching applications, P1 (no pinching) took minimum days to ﬁrst and 50 % ﬁrst pod formation (90.55 and 94.31 days) and diﬀerent yield application of P2 (double pinching at 60 DAS) were maximum length of pod (10.91 cm), pod diameter (2.50 mm), number of pods/ plant (54.87), number of seed/pod (18.61), seed yield/ plant (7.11 g), seed yield/plot (596.40 g) and seed yield/ha (35.51 q), highest TSS (11.73 0Brix) and ascorbic acid (60.16 mg/100g).